A Guide to Nesting Sea Turtles in Florida - Analisa Duran; Ruth Francis-Floyd; Maia Patterson Mcguire; Iskande Larkin (EDIS)
Florida’s coastline provides critical habitat for sea turtle nesting, as it has for millions of years. Throughout the state, three of the seven species of sea turtles in the world have significant nesting populations. Loggerhead, green, and leatherback sea turtles use Florida’s beaches to lay nests each year. This publication provides information on the identification, nesting characteristics, and abundance of each of the common sea turtle species who nest in Florida.